The Application and Evaluation of Effective Quality Management by Objectives in Patient Care for Persistent Vacuum Sealing Drainage. (19th August 2021) - Zhao, Lili; Yang, Jianing; Nie, Mingyang; Wang, Dan; Yan, Guojie; Li, Shuying
Abstract : To investigate the application and evaluation of effective quality management by objectives in patient care for persistent vacuum sealing drainage (VSD), a total of 164 patients with fractures of the hands and feet combined with soft tissue damage admitted to the department of hand and foot surgery in a provincial tertiary hospital from January 2018 to January 2020 were selected as study subjects. The patients were randomly divided into observation and control groups based on the types of fractures, with 82 patients in each group, and both groups underwent VSD surgery for treatment. Both of the groups were cared for VSD using the original nursing model and were compared in terms of treatment compliance, wound recovery, the occurrence of complications, and patient satisfaction with nursing work. The treatment compliance of patients in the observation group was higher than that of the control group (P  < 0.05). Moreover, the wound healing condition in the observation group and the postoperative wound recovery data were better. The hospitalization time and the number of replacement suckers were less (P  < 0.05), which met the requirements of statistical research. This confirmed that the application of quality management by objectives in patient care can improve patient compliance with treatment, promote wound healing, reduce the occurrence of corresponding postoperative complications in patients, and improve patient satisfaction with health nursing, which can be promoted for use in the workplace.